Healthcare Professionals' Attitudes and Practice of Sexual Health Care: Preliminary Study for Developing Training Program - Sung-Hee Ahn (Frontiers in Public Health, 2020)
Health professionals contribute toward addressing the sexual health care (SHC) of cancer patients, given the frequency of contact with their patients. This study investigated nurses' and physicians' SHC attitudes, practices, and educational needs relating to cancer patients' SHC. Using a cross-sectional study design, we assessed South Korean health professionals' attitudes, practice, and training needs related to cancer patients' SHC. Differences in attitudes and practices among the groups were analyzed via an independent-samples t-test, ANOVA, and ANCOVA using SPSS. The demographic characteristics, including sex, marital status, and age, were associated with SHC attitudes and practices. There was a significant difference in the level of nurses' and physicians' attitudes regarding SHC. Compared to nurses, physicians were found to hold a more positive attitude toward SHC. Nurses performed practices pertaining to reproductive care significantly more than physicians after controlling for demographic variables. A small correlation was found between scores on the SHCS–A and the SHCS–P among the groups. Participants' educational needs regarding SHC included changes in sexual function, safe sex during treatment, reproductive health, and sexual counseling approaches. Equipping oncology nurses and physicians with the knowledge to extend their roles by managing cancer patients' sexual function, psychological and social problems, and reproductive care would be effective. Additionally, oncology nurses who are mainly women and relatively younger than physicians ought to enhance their skills in communicating with and counseling male cancer patients.